KAZAKHSTAN’S FUEL AND ENERGY COMPLEX: EFORMS, PROBLEMS,AND PROSPECTS - ESENOVA, Galia (CENTRAL ASIA AND THE CAUCASUS, 2008)
Kazakhstan’s current energy policy is aimed at ensuring the state’s energy independence and raising the efficiency of energy production and consumption. These strategic tasks are being carried out under conditions of sectoral diversification, which is easing the transition from the economy’s raw material to service-technological orientation within the framework of state programs and industrial-innovative development strategies. However, the growing threats to the environment directly related to the development of Kazakhstan’s fuel and energy complex are currently acquiring truly global dimensions and require reconsideration of long-term energy programs from the viewpoint of the state’s environmental security. The past few years have been characterized by high rates of the republic’s economic development. In 2005-2006, the increase in Kazakhstan’s GDP in real terms (10.7%)1 was higher than the forecasts of Standard & Poor’s Ratings Services, Fitch Ratings, and the CIS Statistics Board. The average annual increase rate in the GDP amounted to 10.3%, which was much higher than the mean value for the Commonwealth (7.2%). According to the official data, the amount of investments in subsurface management for 1997-2006 rose five-fold and reached 14.8 billion dollars in 2006. The same year 64.8 million tons of oil and gas were produced in Kazakhstan with a forecast of 62 million tons. The cost volumes of Kazakhstan’s foreign trade, taking into account the presumed average world price of Brent brand oil of 47 dollars a barrel (the GDP deflator amounted to 117.9%), were much higher than the forecast levels: export increased by 37.3% (with a forecast of 8.6%) and import by 36.4% (with a forecast of 24%).2 Products of the fuel and energy complex represented primarily by oil and gas condensate (see Fig. 1) accounted for two thirds of the total export volume (67.5%).